2014
DOI: 10.1007/s12529-014-9421-7
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Survey of Factors Associated with Subjective Feeling of Insomnia, Depression, and Low Health-Related Quality of Life Among Japanese Adults with Sleep Difficulty

Abstract: Among insomnia symptom components, disturbed sleep quality and sleep onset insomnia may be specifically associated with subjective feelings of the disorder. The existence of a depressive state could be significantly associated with not only subjective insomnia but also mental and physical QOL. Our results also suggest that different components of sleep difficulty, as measured by the PSQI, might be associated with mental and physical QOL and depressive status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…Subjects provided informed consent via the questionnaire website. The sample of the present study was consistent with our previous study investigating the factors associated with the awareness of insomnia and deteriorated quality of life as well as depression [20].…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…Subjects provided informed consent via the questionnaire website. The sample of the present study was consistent with our previous study investigating the factors associated with the awareness of insomnia and deteriorated quality of life as well as depression [20].…”
Section: Methodssupporting
confidence: 91%
“…Considering this, we set out to investigate the impact of usage of high doses and multiple kinds of hypnotics and their associated factors via a web-based questionnaire survey [20] targeting the Japanese general population with insomnia symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle changes associated with retirement, the increased incidence of health problems and the use of multiple medications (polypharmacy), comorbid conditions such as dementia and Alzheimer are at increased risk of disrupted sleep (National Sleep Foundation, ; Shrestha, Shrestha, & Khanal,; Pathy et al, ). If not tended to legitimately, insomnia itself incites numerous different diseases and causes significant morbidity, negative impact on well‐being, as well as degrades the quality of life (Aritake et al, ; National Sleep Foundation, ).…”
Section: Introductionmentioning
confidence: 99%
“… It was shown that subjective feeling of insomnia are closely connected with bad health and life quality [20];  It was determined that subjective perception of health and psychological welfare are closely interconnected [26]. In practicing of sports and physical exercises subjective sensations permit to raise the quality of training.…”
Section: Introductionmentioning
confidence: 99%